Tissue-resident memory T cells in renal autoimmune diseases - Ginsberg, Pauline; Panzer, Ulf; Asada, Nariaki (Frontiers in Immunology, 2023)
The discovery of tissue-resident memory T cells (TRM cells) reinterpreted the potential of human tissue-specific immunity. Following T cell receptor (TCR) activation and clonal expansion, effector T cells migrate to peripheral tissues where they remain long-term and differentiate to TRM cells after antigen clearance. This allows for prompt immunological responses upon antigen re-encounter. In addition to their protective properties in acute infections, recent studies have revealed that TRM cells might lead to aggravation of autoimmune diseases, such as lupus nephritis (LN) and anti-neutrophil cytoplasmic antibody (ANCA)-associated glomerulonephritis (GN). These diseases present as proliferative and crescentic glomerulonephritis (cGN), which is a life-threatening condition leading to end-stage renal disease (ESRD) if left untreated. A better understanding of renal TRM cells might lead to identifying new therapeutic targets for relapsing autoimmune diseases of the kidney. In this review, we summarize the current knowledge of renal TRM cells and discuss their potential pathophysiological roles in renal autoimmune diseases.